Culture, Competence and Intercultural Competence: Global and Local Diversities in Intercultural Discourse - Strugielska, Ariadna; Piątkowska, Katarzyna (HERMES - Journal of Language and Communication in Business, 2018)
Despite the plethora of definitions and models of intercultural competence (IC), researchers still face challenges, among which bridging gaps between worldwide trends and local flows in intercultural discourse appears to be an essential goal if definitions and models of IC are to be exhaustive. The present paper summarizes trends in approaches to competence, culture and IC as presented in two types of discourse, global and local, pointing to incongruities between the two viewpoints. An analysis of intercultural research reveals that as opposed to global discourse, which is holistic in nature, local discourse is more modular. It remains an empirical question how these two discourses, and the centripetal and centrifugal forces that come with them, will permeate each other. Thus, the analysis highlights the need to enhance communication among researchers in order to manage multiple approaches, both global and local, and incorporate them into intercultural discourse.